PEMBUATAN MEMBRAN SELULOSA ASETAT DARI PULP ABACA (MUSA TEXTILIS) - Wafiroh, Siti
The development of membrane technology for separation processes in Indonesia is not as fast as in developed countries due to the lack of membrane materials. The purpose of this research is to look for the alternatives of membrane materials by exploring the use of natural resources in Indonesia. Bleached Abaca (Musa textilis) pulp is one of non wood cellulose sources which can be used for producing cellulose acetate (CA). Cellulose has been acetylated during 3.5 hours at 40 °C and hydrolyzed during 20 hours to produce CA having an acetyl content of 40.23%. Analysis of FTIR showed the characteristics of acetyl group at 1238 cm-' and the obtained CA has a relative molecular mass 4.5 x 104. The melting point of Abaca CA obtained by DTA is 386.29°C while commercial CA is 370.6 °C. XRD analysis indicated that Abaca cellulose has a degree of crystallinity of 65% while Abaca CA and commercial CA have degree of crystallinity of 14.9 % and 15.7% respectively . CA membrane were made by phase inversion method with optimal composition : 14 wt% CA, 78 wt% acetone and 8 wt% formamide with water as media of coagulation at 4°C. The water flux at 2 atm was 39.21 ± 0.30 L.m 2.h-' for Abaca CA membrane and 2.82 ± 0.18 L.m 2 .h-' for commercial ones. MWCO was 4.10 x 105 for Abaca CA membrane and 3.57 x 105 for commercial CA membrane. The bursting strength indicated that both Abaca CA and commercial CA membranes showed similar mechanical properties. The SEM photographs showed that commercial CA membranes have denser pore area than Abaca CA membranes. Although Abaca CA and commercial CA membranes had the same efficiency in clarification of turbid water with 100% rejection of Fe3+ ions, the permeability of Abaca CA membranes were higher than that of commercial ones